Prevalence, virulence gene profile and antibiogram of Campylobacter jejuni from fresh vegetables in Mymensingh, Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2023)
This study aimed to investigate Campylobacter jejuni, a major cause of food-borne bacterial infections worldwide, in fresh vegetables from five upzillas (Mymensingh, Trishal, Bhaluka, Muktagacha, and Fulbaria) in the Mymensingh district between July 2020 and April 2023. Using cultural, biochemical, and molecular techniques, 100 fresh vegetable samples (including tomato, carrot, cucumber, green chili, and coriander) were examined for C. jejuni. The isolates were further tested for virulence genes and antimicrobial susceptibility. Out of the 100 samples, 23% were confirmed as C. jejuni, by 16S rRNA gene-based polymerase chain reaction and all were found to be virulent with cytolethal distending toxins (cdtA, cdtB and cdtC genes). Antibiotic susceptibility testing revealed resistance to amoxicillin (47.83%), tetracycline (43.48%), and streptomycin (39.13%) among the isolates. However, ceftriaxone and ciprofloxacin were effective against 47.83% and 43.48% of the isolates, respectively. Moreover, 52.17% of the isolates were sensitive to erythromycin. Alarmingly, 34.78% of the C. jejuni isolates exhibited multidrug resistance (MDR) with eight different antibiotic resistance patterns, including four MDR patterns. These findings highlight the presence of virulent and antibiotic-resistant C. jejuni in fresh vegetables, emphasizing the need for monitoring and control to ensure food safety and public health issues.Asian Australas. J. Food Saf. Secur. 2023, 7 (2), 62-72